Critical Elements on International Aid in Colombia’s Magdalena Medio - Edgar Alberto Zamora Aviles (Íconos)
The study proposes some critical elements on international aid, in particular on European aid, in the Magdalena during the first decade of the 21st century. Beginning with the observation that capital flows of international development aid are not politically neutral and are conditioned by the geopolitical and geo-economic interests of donors, we maintain that aid in this region has contributed to the consolidation of new capitalist spaces in favor of global accumulation and in detriment the proposals for territorial development that the communities in this region have constructed. This process has operated under distinct modalities of accumulation by dispossession in the midst of the humanitarian crisis that the development of social and armed conflict has generated. In the Magdalena Medio, one of the most prominent scenarios of dispossession is that of palm agroindustry.